2014
DOI: 10.1007/s13197-014-1566-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical and physical properties of Latin American wheat flour based tortillas substituted with different levels of distillers dried grains with solubles (DDGS)

Abstract: Tortilla is the most popular type of bread both in South and Central America. Since the demand for this bread among different classes of society is significant, improving its nutrient content could be important. Distillers dried grains with solubles is good source of fiber and protein, and can be used in the fortification of tortilla. In this study, three levels of DDGS (0, 10 and 20 %) were substituted for wheat flour and the physical and chemical properties of the resulting products were evaluated. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Liu et al (2011) reported that DDGS in cornbread induced a decrease in brightness ( L *) and yellowness ( b *), as well as an increase in redness ( a *). These results were consistent with the findings of Tsen et al (1983), Rasco, Downey, and Dong (1987), Singh, Liu, and Vaughn (2012), and Pourafshar et al (2014a).…”
Section: Resultssupporting
confidence: 92%
“…Liu et al (2011) reported that DDGS in cornbread induced a decrease in brightness ( L *) and yellowness ( b *), as well as an increase in redness ( a *). These results were consistent with the findings of Tsen et al (1983), Rasco, Downey, and Dong (1987), Singh, Liu, and Vaughn (2012), and Pourafshar et al (2014a).…”
Section: Resultssupporting
confidence: 92%
“…Tortillas are unfermented flat maize breads, with a soft, flexible, and easy to fold and roll structure and of various colors, depending on the flour and maize source [5]. In Mexico, there are more than 52 species and more than 350 cultivars/colors per species; they are called natives and are cultivated in traditional peasant farming systems, such as the cornfield, as well as genetically improved maize hybrids cultivated in intensive production systems with less costs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment or improvement of nutritional attributes of tortillas has focused in terms of protein, dietary fibre and or antioxidant capacity. Whole wheat-flour, oat:inulin mixes, whole and defatted soy flour, whole kamut flour, carrot juice, whole waxy barley, pinto bean flour, sprouted whole-wheat flour, sorghum polyphenols, distillers dried grains with solubles are some ingredients previously evaluated in tortilla (Scazzina et al 2008;Anton et al 2009;Prasopsunwattana et al 2009;Barros et al 2010;Heredia-Olea et al 2015;Pourafsar et al 2015;Liu et al 2017;Perez-Carrillo et al 2015;Serna-Saldivar 2016). In all cases, the challenge is to retain tortilla quality attributes like colour, texture and organoleptic acceptance.…”
Section: Introductionmentioning
confidence: 99%